Regional Labor Market Adjustments in the United States - Dao, Mai.; Furceri, Davide; Loungani, Prakash (Washington, D.C. : International Monetary Fund, 2014)
We examine patterns of regional adjustments to shocks in the US during the past four decades. We find that the response of interstate migration to relative labor market conditions has decreased, while the role of the unemployment rate as absorber of regional shocks has increased. However, the response of net migration to regional shocks is stronger during aggregate downturns and increased particularly during the Great Recession. We offer a potential explanation for the cyclical pattern of migration response based on the variation in consumption risk sharing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet